The Influence of Tariqa in the Tablighi Jamaat Congregation: Principles and Practices - Muhammad Azizzullah Ilyas (JURNAL ILMIAH SYI'AR, 2022)
Tablighi Jamaat movement has several proselytizing agendas that are not explicitly stated, but can be seen from the phenomenon of the Tablighi Jama'ah ritual practice which in some aspects carries the values of tarekat and Sufism. Seeing this phenomenon, the research was conducted with the aim of analyzing the tarekat and Sufi aspects in the Da'wah of the Tablighi Jama'at. This research is a qualitative type with participatory observation data sources, interviews and enriched with library data, the sample of informants is selected by the snowball technique. The data obtained were collected, grouped and analyzed for further description descriptively. The results of the study found the Tablighi Jamaat had practices that were sourced from the practices of the congregation. The Chistiyah Order is the dominant order as a reference in principles and practices. Another order that also influenced was the Naqhsabandiyah. For the Syadziliyah congregation there are similarities in zikr and far away but further analysis is needed. Meanwhile, the Naqhsabandiyah-Khalidiyah later influenced the Tablighi Jamaat in Indonesia.